PENGARUH KASEIN HIDROLISAT DAN INTENSITAS CAHAYA TERHADAP PRODUKSI BIOMASSA DAN ALKALOID CANTHINONE DI DALAM KULTUR SUSPENSI SEL PASAK BUMI (Eurycoma longifolia Jack) - Siregar, Luthfi Aziz Mahmud; Keng, Chan Chan; Lim, Boey Peng (UI Scholars Hub, 2010)
Effects of Casein Hydrolisate and Light Intensity on Production of Biomass and Canthinone Alkaloid in Cell Suspension Cultures of Pasak Bumi (Eurycoma longifolia Jack). A study on the effect of several concentrations of casein hydrolysate and light intensity to produce biomass and canthinone alkaloid in cell suspension culture of Pasak Bumi (Eurycoma longifolia Jack) was conducted. The research was an experimental study with block random design non factorial. For study of casein hydrolysate was used 8 (eight) of concentration treatments, i.e. 0.00, 0.10, 0.25, 0.50, 0.75, 1.00, 2.00, dan 5.00% (w/v). Beside for study of different light intensity effect was used five of light intensity, i.e. 0, 190, 290, 585, and 1525 lux. The results showed that addition 0.1–2.0% (w/v) of casein hydrolysate into culture medium did not show the effect on production of cell biomass compare with without casein hydrolysate. Total of alkaloid produce increased two fold in the culture medium containing 0.1% casein hydrolysate. The medium with addition 5% casein hydrolysate significantly decrease of increased fresh weight, dry weight and total of alkaloid compare with medium without or additions of casein hydrolysate at 0.1–2.0% concentration. Besides, the modifications on light intensity (0–1525 lux) did not effect the production of cell biomass in culture medium, but the place of E. longifolia Jack cell suspension culture at light of 1525 lux was found have to stimulate increased the total of 9- methoxycanthin-6-one in cells.